Analisis Realisasi Pendapatan Daerah Sektor Perkebunan (Studi Kasus pada Dinas Pendapatan Daerah Kabupaten Bireuen) - Muklir Muklir (Jurnal Aplikasi Manajemen, 2010)
The main characteristic which shows an autonomous territory able to be autonomous lied on local government financial capabilities, it means that autonomous district must have competency and authority to discover, manage, and use its own financial resources adequately for funding local government’s operation. District original revenue (PAD) becoming a financial resource which can fund public and apparatus expenditure. This research employed qualitative methods, data collected through observations, interviews, and documentations. Whereas technical data analysis employed interactive model’s which are including data reduction, data presentation and conclusion drawing. This research results found that plantation sector still unable to support special autonomy implementation, unable to fund routine daily expenditures. The acquisitions of PAD from plantation sector still lower than the immense nominal of districts expenditures. Thus, the realization of PAD from plantation sector must be improved.